Ocean Sustainability through Blue Finance: A Strategic Governance Systematic Bibliometric Review - Betharia Efriani; Rahellia Panjaitan (Institut Teknologi dan Bisnis Asia Malang, 2026)
Research Objective, this study maps the development of knowledge, scientific trends, and future research directions in blue finance and ocean sustainability using a Systematic Literature Review (SLR) approach. Data and Methodology, a total of 739 Scopus-indexed articles (1999–2025) were analyzed using bibliometric techniques to examine publication growth, author productivity, collaboration networks, sources, and citation patterns, yielding 17,302 citations. Key Thematic Findings, the analysis identifies dominant thematic clusters, including blue economy, sustainable marine finance, marine conservation, and strategic ocean governance. Publication trends increased significantly after 2015, aligning with the global emphasis on the SDGs, particularly SDG 14, SDG 13, and SDG 12. Emerging Trends, ESG principles are increasingly embedded in blue finance research, emphasizing environmental risk management, social inclusion of coastal communities, and transparent marine governance. Keyword co-occurrence analysis indicates a shift from purely ecological perspectives toward an integrated economic, social and governance sustainability framework. Research Implications, these findings provide a comprehensive overview of the scientific landscape of blue finance and ocean sustainability and highlight future research opportunities focused on strengthening ESG integration and supporting SDG-oriented sustainable ocean economic development.